Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1177/030098589703400110
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Equine Herpesvirus-1 Antigen in Neurons and Astrocytes of Horses with Acute Paralysis

Abstract: Equine herpesvirus-1 (EHV-1) infection in a few widely scattered neurons and astrocytes plus endothelial cells in brain and spinal cord of two horses with naturally occurring paralytic disease was demonstrated by use of an immunoperoxidase technique. These horses were euthanatized less than 48 hours after the onset of clinical signs. No staining for EHV-1 was demonstrated in brain or spinal cord of three horses that had a longer duration of clinical disease or in two uninfected horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The characteristic lesions in horses infected with EHM are vasculitis of small vessels and thrombosis, resulting in ischaemic damage to the CNS. Although EHV-1 is not considered primarily neurotropic, it has been reported that the virus can induce lesions in neurons and astrocytes (12). Moreover, the present study found positive samples from the CNS or CSF by virus isolation and PCR.…”
Section: Case Reportsupporting
confidence: 54%
“…The characteristic lesions in horses infected with EHM are vasculitis of small vessels and thrombosis, resulting in ischaemic damage to the CNS. Although EHV-1 is not considered primarily neurotropic, it has been reported that the virus can induce lesions in neurons and astrocytes (12). Moreover, the present study found positive samples from the CNS or CSF by virus isolation and PCR.…”
Section: Case Reportsupporting
confidence: 54%
“…In the natural host, following the primary respiratory involvement, the infection of the vascular endothelium with consecutive vasculitis and perivascular ischaemia govern the pathological events. Even in the brain the vascular pathology stands in the foreground, whereas direct virus attack on neurons is exceptional (11–13) or even absent (17). In the mouse, EHV‐1 is endotheliotropic only in extraneural organs, as shown by the presence of vasculitis, and virus antigen expression of vascular endothelia in the lung in our experiments, furthermore, by the occurrence of abortions in virus‐infected pregnant animals, as observed by others (18, 25, 56, 57).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other neuropathogenic alphaherpesviruses, which cause encephalitis via neuronal infection, EHV-1-induced myeloencephalopathy is caused by infection of vascular endothelia of arteries supplying the central nervous system (CNS). The subsequent inflammatory response leads to thrombosis and ischemic damage [5,6]. A sustained and high-level presence of viral DNA in the blood stream, and, by implication, cell-associated viremia, is associated with the development of neurologic disease in EHV-1-infected horses [7,8].…”
Section: Introductionmentioning
confidence: 99%